International encyclopedia of marriage and family - Ponzetti, James J.; Gale Group (New York Macmillan Reference USA, 2003)
Includes articles specific to countries and to religious traditions, examining the history of family life within these cultures and discussing how families have been affected by political and social change.
Rev. ed. of: Encyclopedia of marriage and the family. c1995.
Electronic reproduction.
Keywords: Marriage -- Encyclopedias; Family -- Encyclopedias; Electronic books